Two novel alleles HLA‐A*02:433 and HLA‐A*02:434 identified in Saudi bone marrow donors using sequence‐based typing. (12th June 2014) - Fakhoury, H. A.; Jawdat, D.; Alaskar, A. S.; Al Jumah, M.; Cereb, N.; Hajeer, A. H.
Summary In this report, we present two novel HLA‐A alleles: HLA‐A*02:433 and HLA‐A*02:434. These alleles were identified by sequence‐based typing method (SBT), in two donors for the Saudi Bone Marrow Donor Registry (SBMDR). Allele A*02:433 is identical to A*02:05:01G except for a G to A substitution at nucleotide position 449 in exon 2. This substitution results in glycine to serine substitution at position 83. Whereas, allele A*02:434 is identical to A*02:01:01G except for a C to A substitution at nucleotide position 245 in exon 2, which results in phenylalanine to threonine substitution at position 15. The generation of both alleles appears to be the result of nucleotide point mutation involving 02:01:01 and 02:05:01.